PhD Abstracts. (2nd July 2021) - HUTTON, GRAHAM
Abstract : Many students complete PhDs in functional programming each year. As a service to the community, twice per year the Journal of Functional Programming publishes the abstracts from PhD dissertations completed during the previous year. The abstracts are made freely available on the JFP website, i.e. not behind any paywall. They do not require any transfer of copyright, merely a license from the author. A dissertation is eligible for inclusion if parts of it have or could have appeared in JFP, that is, if it is in the general area of functional programming. The abstracts are not reviewed.